Growth Promoting Effect of Vacuum Sealing Drainage in the Healing Processes of Diabetic Foot Ulcers - Yang H (Dove Medical Press, 2021)
Hui Yang,* Lan Liu,* Gai Li, Yinchen Chen, Dong Jiang, Wei Wang, Tianyuan Wang, Jinshan Sun, Jianfang Che, Dongmei Gu, Meng Lu, Aiping Wang Department of Endocrinology, The Air Force Hospital from Eastern Theater of PLA, Nanjing 210029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Aiping Wang; Meng LuDepartment of Endocrinology, The Air Force Hospital from Eastern Theater of PLA, 1 Malujie Road, Nanjing 210029, People’s Republic of ChinaTel +86-25-80865162Email wap454hospital@163.com; lumeng365@hotmail.comAim: To explore the growth-promoting effect of vacuum sealing drainage (VSD) during the healing processes of diabetic foot ulcers (DFUs).Methods: From November 2018 to December 2019, 38 patients with unilateral DFUs were enrolled in this retrospective study. All patients were divided into two groups according to the use of VSD or not: the VSD group (n=20) and the control group (n=18). The following parameters were used to evaluate the healing process: changes in the mean areas of the ulcers; healing rate (HR); epithelial hyperplasia and angiogenesis as determined by hematoxylin-eosin staining (HE staining); and expression of CD34, CD68 and VEGF as assessed through immunohistochemistry. Perioperative side effects and complications were also recorded.Results: All patients received follow-up and eventually healed. The mean area of wounds was reduced in the VSD group compared to the control group (1.75± 0.64 cm2 vs 0.88± 0.54 cm2, P=0.031). The mean HR of the ulcers in the VSD group was significantly higher than that in the control group (35.23± 2.87% vs 28.78± 1.09%, P=0.017). HE staining showed that the amount of epithelial hyperplasia and angiogenesis increased significantly after VSD, and the immunohistochemistry results showed that the expression of CD34, CD68 and VEGF increased significantly in the VSD group.Conclusion: VSD could significantly accelerate the wound healing process, probably by enhancing the inflammatory response and promoting granulation and angiogenesis in DFUs.Keywords: vacuum sealing drainage, diabetic foot ulcers, wound healing, CD34, CD68, VEGF